Utilizing Support Vector Machines for Early Detection of Crop Diseases in Precision Agriculture a Data Mining Perspective - Saxena, Vinay; Singh, Mala; Saxena, Parul; Singh, Mukesh; Srivastava, Arun Pratap; Kumar, Navneet; Deepak, A.; Shrivastava, Anurag (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research centers on progressing crop infection discovery in accuracy agriculture through the synergistic application of Support Vector Machines (SVM) and information mining strategies. Leveraging SVM’s classification ability and information mining’s design investigation, our strategy includes comprehensive information preprocessing, highlight building, and temporal examination. The study assesses and demonstrates precision through k-fold cross-validation, guaranteeing strong execution over differing subsets. Straightforward demonstrates interpretability is prioritized, improving stakeholder understanding. Moral contemplations, security shields, and inclination relief methodologies are necessary for the research. Vital commitments are drawn from a comprehensive writing audit including machine vision, directed learning-based picture classification, hyperspectral detecting, and imaginative AI applications in agriculture. Future work is imagined to coordinate progressed sensors, investigate gathering approaches, and conduct field validations, emphasizing dynamic demonstrate updating. This investigation adjusts with the exactness of agriculture’s direction towards economical and proficient edit wellbeing administration.